Price Caps, Rate-of-Return Regulation, and the Cost of Capital - Alexander, Ian; Irwin, Timothy (World Bank, Washington, DC, 2012)
This Note compares the effects of price cap and rate-of-return regulation on the risk borne by regulated utilities. It present evidence that price cap regulation subjects firms to greater risks and therefore raises their cost of capital. This result has one clear implication: firms regulated by price caps must be permitted to earn higher returns. If they are not, they will be unable to attract new investment capital and the quality of their service will decline.